Hypnosis, Massage Relaxation, Endorphins And Pain Intensity First Stage of Normal Delivery Primapara BPS Semarang - Melyana N W; Irmawati Irmawati; Sugih Wijayati (Poltekkes Kemenkes Semarang, 2012)
The purpose of this study was to determine the effectiveness of the method of hypnosis, massage and relaxation endorphins to the intensity of pain during on the first stage of Normal Delivery in BPS (Private Practice Midwives) Semarang City area. The research method used was non-equivalent experimental design, a sample of 20 mothers maternity on each - each treatment group. Test used was ANOVA test followed Post Hock Tukey test. These results obtained p-value = 0.001 (significant) followed post hoc Tukey test found significant method of hypnosis to massage endorphins (p = 0.023) and relaxation (p = 0.000), whereas no significant endorphins massage method with a relaxation method (p = 0.370 ). This shows that the method of hypnosis is a method that gives the lowest effects of pain compared with endorphins massage and relaxation.